Central composite design applied to purify lemongrass essential oil using vacuum distillation - Muhammad Dani Supardan; Dewi Ermaya; Hesti Meilina (Syiah Kuala University, 2013)
Vacuum distillation process can be applied for purification of lemongrass essential oil by increasing the concentration of citral in lemongrass essential oil. In this study, the relationship between experimental parameters of purification of lemongrass oil was investigated. The effect of pressure, temperature and pH was examined to determine the best performance of the product yield. CentralComposite Design was applied to optimize the operating parameters of the process. It was found that the product yield of bottom product achieved an optimum level of 98.4% yield at the following reaction conditions, i.e. pressure of 55.9 mbar, temperature of 104.6oC and pH of 4.8